Pengaruh Rasio Mol Minyak : Metanol Terhadap Sintesis Biodiesel Dari CPO (Crude Palm Oil) Menggunakan Katalis La/ZnO - Yumna, Nada Ibtihal; Bahri, Syaiful; Utama, Panca Setia (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
The synthesis of biodiesel is affected by several factors, one of them is the mole ratio of oil to methanol. Producing biodiesel need excess amount of methanol to increase biodiesel yield. The effect of mole ratio of oil to methanol of 1:9; 1:12; 1:18 and the amount of La impregted to ZnO of 1%; 2%; 3%; 6% to the biodiesel yield were studied. The impregnation of La into ZnO was done by maxing La2O3 and ZnO, and then the calcination process was applied for 6 hours at 500 oC using N2 gas. The oxidation process was done for 2 hours at 400 oC using O2 gas. The reduction process was done for 2 hours at 400oC using H2 gas in order to reduce oxygen in La2O3. The esterfication process was done in 1000 cm3 stirred glass reactor, the operating conditions were temperature of 60 oC and time of 60 minutes. After that, the transesterification process was done using the same equipment. The operating conditions were temperature of 60 oC and time of 90 minutes, stirring speed of 400 RPM, and amount of catalyst was 1% (w/w) oil. The highest biodiesel yield of 90.937 % was obtained at the mole ratio of oil to methanol 1:18 and amount of La impregted into ZnO of 6 %. Physical characteristic of biodiesel obtained were density of 881 kg/m3, kinematic viscosity of 3.53 mm2/s, acid number of 0.423 mg-KOH/g biodiesel and flash point of 148 oC which is in accordance to the standard of Indonesian Biodiesel (SNI 04-7128-2015).Keywords: biodiesel, CPO, La/ZnO catalyst, transesterification